Unveiling the Launaea nudicaulis (L.) Hook medicinal bioactivities: phytochemical analysis, antibacterial, antibiofilm, and anticancer activities - Elkady, Fathy M.; Badr, Bahaa M.; Hashem, Amr H.; Abdulrahman, Mohammed S.; Abdelaziz, Amer M.; Al-Askar, Abdulaziz A.; AbdElgayed, Gehad; Hashem, Hany R. (Frontiers in Microbiology, 2024)
The commonly used antimicrobial agents are no longer effective due to their overuse or misuse. Also, many medicinal plant extracts can combat infectious diseases due to their main active constituents or secondary metabolites. The current study aimed to assess the bioactivities of Launaea nudicaulis Leaf Extract (L. nudicaulis LE) against different multidrug resistant (MDR) Pseudomonas aeruginosa (P. aeruginosa) isolates, also to evaluate its anticancer activity. The ethyl acetate extract of Launaea nudicaulis (LN) leaf was analyzed using GC-MS, which identified 27 key bioactive chemical compounds. The major constituents found were: 7-acetyl-6-ethyl-1,1,4,4-tetramethyltetralin, isopropyl myristate, thiocarbamic acid, N,N-dimethyl, S-1,3-diphenyl-2-butenyl ester, hahnfett, cyclopentane acetic acid, 3-oxo-2-pentyl-, methyl ester, hexadecanoic acid, and dotriacontane. Our investigation demonstrated that LN leaf was a rich source of various other important phytochemicals, including phenolic acids, tannins, saponins, and steroids. The relative biosafety of L. nudicaulis LE was concluded from the elevated inhibitory concentration 50 (IC50) of 262 µg/ml calculated from the cytotoxicity assay against the Wi-38 normal cell line. Conversely, 12.7 and 24.5 µg/ml were recorded as a little IC50 of the tested extract against the MCF-7 and Hep-G2 cancerous cell lines, respectively reflecting their potent activity against the tested cancerous cell lines. Microbiologically, the susceptible P. aeruginosa isolates to the tested extract showed growth inhibition zone diameter, in well diffusion assay, at a range of 11.34±0.47 to 26.67±0.47 mm and percent inhibition (PI) of 50-106.2% reflecting its acceptable activity. Additionally, the broth microdilution assay recorded MIC and MBC in the range of 15.625-1000 µg/mL and 125-1000 µg/mL, respectively. In conclusion, L. nudicaulis LE revealed promising activity and high selectivity against P. aeruginosa. Moreover, the extract exhibited natural anticancer activities with safe low concentrations which indicated its a superior candidate for future studies of its active constituents.